(untitled) (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2024)
This study analyzes the concept of female leadership in the virtual space, focusing on Surah An-Nisa’ verse 34, presented through the YouTube channel Kajian Tafsir Al-Ma’rifah by Ustadz Musthafa Umar. The main aim of this study is to explore the discourse surrounding female leadership in the digital world, a topic that often sparks interesting discussions and even ongoing polemics among both men and women. Surah An-Nisa’ verse 34 is one of the frequently studied verses in the discourse on gender relations and leadership roles in Islam, addressing male leadership over women, including aspects of financial support and protection. This study uses a qualitative method with a content analysis approach on the research video’s content. Data were collected through the documentation method, referring to relevant sources. In his interpretation, Musthafa Umar argues that men (husbands) are the leaders of the family, likening them to the captain of a ship, where the husband is the captain. The husband is expected to be better than those he leads, as otherwise, he would not be fit to be a leader. There are two main reasons: first, men are endowed with physical advantages, and second, men are obligated to provide financial support to their wives and families. The research findings indicate that Musthafa Umar’s interpretation of this verse tends to show gender bias, arising from a textual approach that leans towards classical interpretations. This study also reveals how virtual platforms like YouTube serve as a medium for spreading and discussing tafsir, which can influence the audience’s perceptions.